The Indonesian Adaptation of Developmental Crisis Questionnaire-12 (DCQ-12) - Aprodita, Nindya Putri; Rasyida, Afinnisa; Mardi Rahayu, Maria Nugraheni (Journal of Educational, Health and Community Psychology, 2024)
The developmental crisis in early adulthood, often referred to as the Quarter-Life Crisis, has garnered significant attention in recent years. Although widely discussed in mass media and popular writings, there is a lack of a well-established psychological scale to measure this crisis in Indonesia. This study aims to examine the psychometric properties of the Indonesian adaptation of the Developmental Crisis Questionnaire (DCQ-12) developed by Petrov et al. (2022) for assessing early adulthood developmental crises. The DCQ-12 instrument consists of twelve statements divided into three factors: Disconnection and Distress, Lack of Clarity and Control, and Transition and Turning Point. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) are used in the test. This research involves 300 Indonesian early adult participants (mean age = 31.81 years, SD = 6.72, 90% female) for EFA testing and 248 participants (mean age = 25.2 years, SD = 5.32, 78.2% female) for CFA testing. The results indicate that the three-factor structure of the ten items of the Indonesian version of the DCQ has psychometric properties classified as "acceptable fit," making it suitable for research on developmental crises in early adult individuals. Future research should explore the psychometric properties of this instrument in other population groups, such as middle-aged and older adults, and consider implications for interventions or support programs